Can Photosynthetic Performance of Oat (Avena sativa L.) Plants be Used as Bioindicator for Their Proper Growth Conditions? - Renata Tobiasz-Salach (Science Faculty of Chiang Mai University, 2019)
ecently, oat (Avena sativa L.) plants are cultivated as worldwide functional food. The aim of this study was to analyse the response of photosynthetic apparatus of naked and hulled oat cultivars grown under different nitrogen fertilization dosage as well as different weather and soil conditions (different locations). Our analysis showed a significant influence of all studied experimental factors i.e. location, year, nitrogen dosage, cultivar/strain, leaf position on some selected chlorophyll fluorescence (ChlF) parameters and grain yield. Soil and climatic conditions/ environments had the largest and statistically significant contribution to the variability of the analysed ChlF parameters, while the genotype (cultivar/strain) effect was the highest for grain yield. For other effects, the values were much smaller. Our results suggest that chlorophyll fluorescence measurements should be used in oat field experiments as a trustable and useful tool to study the reactions of plants photosynthetic apparatus under natural environments and to predict its yielding. Moreover, it can help to establish the optimal growth conditions for individual cultivars, including fertilizers’ dosing.